The impact of adapted soccer program on psychosocial behavior in adolescents with Down syndrome - Perić, Dušan; Milićević Marinković, Bojana (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Numerous studies have proven the significant positive impact of regular physical activity on the condition of people with intellectual disability. In practice, various adapted sports activities are increasingly used for children and adolescents with disabilities. Objectives. The current feasibility study determined the effect of soccer program on some psychosocial characteristics in adolescents with Down syndrome. Methods. 20 adolescents were recruited and randomized into two groups (the experimental group vs. the control group). Adolescents placed in the experimental group followed an adapted soccer program twice a week for 16 weeks. Adolescents placed in the control group continued with their usual daily routine during the experimental period. The level of aggression, attention problems, the level of anxiety and depression, and social problems were assessed. Results. The experimental group had significant improvements in all psychosocial variables. At the same time, no significant changes were registered in the control group. Conclusion. The results suggest that the soccer program can decrease the level of aggression, anxiety and depression, increase attention and improve social behavior in adolescents with DS.